2011
DOI: 10.1371/journal.pone.0016070
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Zipper-Like Coiled-Coil Domains Are Necessary for Homotypic Dimerization of Plant GAGA-Factors in the Nucleus and Nucleolus

Abstract: GAGA-motif binding proteins control transcriptional activation or repression of homeotic genes. Interestingly, there are no sequence similarities between animal and plant proteins. Plant BBR/BPC-proteins can be classified into two distinct groups: Previous studies have elaborated on group I members only and so little is known about group II proteins. Here, we focused on the initial characterization of AtBPC6, a group II protein from Arabidopsis thaliana. Comparison of orthologous BBR/BPC sequences disclosed tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 76 publications
6
70
0
Order By: Relevance
“…By contrast, plants that contained the reporter construct in which five C-boxes were mutated displayed ectopic expression in the carpel and stamens, suggesting that the number of BPC binding sites is important for correct gene expression. Our yeast interaction studies showed that BPC proteins of class I can interact with each other, and the fact that those of class II also interact between them and with those of class I (Wanke et al, 2011) further supports the idea that multiple DNA interactions combined with BPC protein-protein interactions will induce conformational changes into the STK promoter region, also corroborated by the previous reported in vitro TPM analysis (Kooiker et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…By contrast, plants that contained the reporter construct in which five C-boxes were mutated displayed ectopic expression in the carpel and stamens, suggesting that the number of BPC binding sites is important for correct gene expression. Our yeast interaction studies showed that BPC proteins of class I can interact with each other, and the fact that those of class II also interact between them and with those of class I (Wanke et al, 2011) further supports the idea that multiple DNA interactions combined with BPC protein-protein interactions will induce conformational changes into the STK promoter region, also corroborated by the previous reported in vitro TPM analysis (Kooiker et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Expression of full-length fusion proteins was verified by immunoblot analysis (see Supplemental Figure 9 online). As shown in Figure 5, cry2, CIB1, and all four SPAs localized to nuclei as additionally verified using the mCherry-NLS reporter (Wanke et al, 2011). Moreover, the pictures from the merged GFP and RFP channels showed that cry2 colocalizes with CIB1 and all four SPAs.…”
Section: Cry2 Directly Interacts With Spa1 In Nuclei Of Living Cellssupporting
confidence: 63%
“…Afterwards some plant material was harvested followed by protein extraction for immunoblot analysis. In vivo interaction studies of the full-length fusion proteins were measured by FRET-FLIM with a confocal stage scanning microscope according to Wanke et al (2011). For each tested combination of fusion proteins, three measurements of fluorescence lifetime decays were recorded and mean values estimated.…”
Section: Confocal Laser Scanning Microscopy and Fret-flim Studiesmentioning
confidence: 99%
“…All FLIM measurements were performed as previously described (Wanke et al, 2011), with the following modifications for CFP-YFP FRET. A pulsed 440-nm diode laser (Picoquant LDH-D-C-440), operating at a repetition rate of 20 MHz, was used for excitation, in conjunction with LD01-439/8-12.5 (Semrock) cleanup interference filters.…”
Section: Fret-flim Analysismentioning
confidence: 99%